Dynamic state of ecosystem carrying capacity under island urbanization: a case study of Pingtan Island in the Southeastern coast of China - Gao, Sheng; Sun, Huihui; Cao, Guangxi; Zhao, Lin; Wang, Runjie; Xu, Min (Journal of Environmental Engineering and Landscape Management, 2020)
The assessment of ecological environment during the large-scale development of islands is a major topic in the study of current coastal islands. Choosing the appropriate assessment method to evaluate the suitability of carrying capacity of islands and making relevant suggestions are significant to the sustainable development of islands. Ecological footprint method is used to analyze the ecological carrying capacity of Pingtan Island (PI) from 2005 to 2016 for promoting the coordinated rational development and construction and ecological environment of the island. Although PI is in rapid urban development and construction, the island maintains secure and stable ecological conditions. PI is used as a research case to analyze the sustainable development of the ecological environment through the carrying capacity of the island ecosystem.